INTEGRATION DESIGN OF PSYCHO CYBERNETICS TRAINING AND ENTREPRENEURIAL SKILLS - Anna Marganingsih; Emilia Dewiwati Pelipa; Yunita Astikawati (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
The progress of a country is supported by the number of educated graduates and entrepreneurs in the country. In fact, there are still many graduates who after graduating from higher education are reluctant to become entrepreneurs. Therefore, it is necessary to conduct training to foster student entrepreneurship motivation. The aims of this research is to create a training design that is able to stimulate student entrepreneurial motivation, namely the Integration of Psycho Cybernetics Training and Entrepreneurial Skills. The method used in this research is quantitative by using five research steps, namely literature study, focus group discussion, expert consultation, revision and limited experimentation. Limited experimental analysis was carried out with statistical tests where the results of the pre-requisite test showed that the data were not normally distributed so that hypothesis testing was carried out using non-parametric statistical tests. The results of the hypothesis test showed a significant value of 0.000 <0.05 which means alternate hypothesis is accepted and the null hypothesis is rejected. Thus the Integration Design of Psycho Cybernetic Training and Entrepreneurial Skills is able to stimulate student entrepreneurship motivation